Qualidade do serviço público odontológico no Brasil: a percepção de usuários e profissionais da saúde - Bordin, Danielle [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Studies aimed at understanding the different dimensions involved in the perception of users and health professionals allow wider and reliable regarding the current health assessment model. The aim of this study is to analyze user' satisfaction with the Brazilian public dental services, in its different dimensions of care and relate them to the socioeconomic and demographic conditions; and analyze the prediction of professionals about the satisfaction of users. It is a cross-sectional survey, quantitative, developed in the city of Ponta Grossa, Paraná. Study participants: 461 users, 30 dentists (CD), 22 technicians/assistants oral health (TSB/ASB) and 133 community health workers (ACS). It was used interview with structured questionnaire. The user profile was associated with overall satisfaction with the chi-square test. The questions were evaluated individually and grouped into domains. To analyze an index from 0 to 1 was created valuing the answers: satisfied (value 1), more or less (value 0,5) and dissatisfied (value 0) and applied the Kruskal-WallisTest with Dunn's post-test. Users showed that were satisfied in relation to public dental services (0.80). Elderly users, with low education and male, tended to evaluate more positively the services (p<0.05). The users added more satisfaction to the 'physical structure' (0.90) and 'relation and communication' (0.85) domain. The domain 'organization of services' was the one that received the worst rating among all classes of the subjects interviewed. The CD and TSB/ASB have exposed greater satisfaction than revealed by users in the most of the variables evaluated, however, no statistically significant difference (p>0.05). The ACS have exposed a vision that users would be less than pleased to be demonstrated, significant difference for: overall satisfaction (p<0.05); 'quality of clinical care' (p<0.001); 'orientation to the patient...

Estudos voltados para o entendimento das diferentes dimensões que envolvem a percepção de usuários e de profissionais da saúde permitem uma avaliação ampla e fidedigna do modelo de saúde vigente. Objetivou-se neste estudo verificar a satisfação de usuários com o serviço público odontológico brasileiro, em suas diferentes dimensões de cuidado, e relacioná-las com as condições socioeconômicas e demográficas; e analisar a predição de profissionais acerca da satisfação de usuários. Trata-se de uma pesquisa transversal, quantitativa, desenvolvida no município de Ponta Grossa, Paraná. Compuseram a amostra: 461 usuários, 30 cirurgiões-dentistas (CD), 22 técnicos/auxiliares em saúde bucal (TSB/ASB) e 133 agentes comunitários de saúde (ACS). Realizou-se entrevista com questionário estruturado. O perfil do usuário foi associado à satisfação geral pelo teste Qui-quadrado. As questões foram avaliadas individualmente e agrupadas em domínios. Para análise foi criado um índice de 0 a 1 valorando as respostas em: satisfeito (valor 1), mais ou menos (valor 0,5) e insatisfeito (valor 0) e aplicado o teste Kruskal-Wallis com pós-teste de Dunn's. Os usuários demonstraram-se satisfeitos em relação ao serviço público odontológico (0,80). Idosos, com baixa escolaridade e do sexo masculino, tenderam a avaliar de forma mais positiva os serviços (p<0,05). Os usuários agregaram maior satisfação aos domínios 'estrutura física' (0,90) e 'relação e comunicação' (0,85). O domínio 'organização dos serviços' foi o que recebeu a pior avaliação entre todas as classes de sujeitos entrevistados. Os CD e TSB/ASB expuseram satisfação maior do que a revelada pelos usuários na maioria das variáveis avaliadas, contudo, não houve diferença estatisticamente significante (p>0,05). Os ACS expuseram uma visão de que os usuários estariam menos satisfeitos do que demonstraram...
Keywords: Cuidados primários de saúde; Saúde bucal; Satisfação do paciente; Pessoal da area médica; Primary health care